Immunomodulating effects of peptidic fractions issued from milk fermented with Lactobacillus helveticus - Leblanc, Jean Guy Joseph (2002)
The effect of peptides released during the fermentation of milk on the humoral immune system and on fibrosarcoma growth was studied. Lactobacillus helveticus was able to release peptidic compounds during milk fermentation due to its high proteolytic activity, as was shown by the degree of proteolysis and size-exclusion HPLC elution profiles. Three fractions of these compounds were separated and fed to mice during different periods (2, 5, and 7 d). The humoral immune response was assessed by following the number of IgA-secreting cells, and the antitumor activity was monitored by studying the regression of subcutaneously implanted fibrosarcomas. Feeding during 2 and 7 d with the medium-sized fraction (Fraction II) significantly increased the IgA-producing cells in the intestines, whereas feeding with the large compound fraction (Fraction I) during 5 d and the small compound fraction (Fraction III) during all three feeding periods provided similar increases. A double dose of Fraction II showed the highest IgA-producing cell count. The increase by Fraction III was shown to be caused by the presence of L-Tryptophan. Fraction II significantly decreased the size of fibrosarcoma when previously fed during 7 d, and feeding with Fraction I during 5 d decreased significantly its size after 35 d of growth. Although the mechanisms by which lactic acid bacteria enhance the immune system are not clear, this study clearly shows that bioactive compounds released in fermented milks contribute to the immunoenhancing and antitumor properties of these products. The release of bioactive peptides by lactic acid bacteria can have important implications on the modulation of the cellular immune response.